2022
DOI: 10.3233/wor-211018
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and behaviour of dentists working during the COVID-19 pandemic: A cross-sectional survey

Abstract: BACKGROUND: The coronavirus disease 2019 (COVID-19) has immensely affected the world’s population at physical and psychosocial levels. Dentists are no different from other healthcare providers, as they are equally if not more exposed to the threat of getting infected. OBJECTIVE: To assess the experience and behavior of public and private sector dentists practicing during the COVID-19 pandemic and their knowledge about it. METHODS: A cross-sectional survey was conducted online by sharing google forms through em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
1
1
0
2
Order By: Relevance
“…The dentists in this survey were generally less knowledgeable (67.3%) about disinfection practices, which was similar to another survey where only 66.8% had adequate knowledge of disinfectants that should be used [ 11 ]. Some of the more recent studies investigating knowledge, attitudes and behavior conducted in 2021 (around the same time as our study) also showed good compliance with WHO and CDC guidelines [ 20 ] and good scores of knowledge and preventive practice [ 21 ], and are consistent with our findings. The high levels of knowledge and preventive practice may be due to the fact that our survey was conducted almost 15 months into the pandemic and most dentists were receiving their information from a variety of established sources at that time such as WHO (96.8%), CDC (75.3%) and the local Ministry of Health (85.7%).…”
Section: Discussionsupporting
confidence: 92%
“…The dentists in this survey were generally less knowledgeable (67.3%) about disinfection practices, which was similar to another survey where only 66.8% had adequate knowledge of disinfectants that should be used [ 11 ]. Some of the more recent studies investigating knowledge, attitudes and behavior conducted in 2021 (around the same time as our study) also showed good compliance with WHO and CDC guidelines [ 20 ] and good scores of knowledge and preventive practice [ 21 ], and are consistent with our findings. The high levels of knowledge and preventive practice may be due to the fact that our survey was conducted almost 15 months into the pandemic and most dentists were receiving their information from a variety of established sources at that time such as WHO (96.8%), CDC (75.3%) and the local Ministry of Health (85.7%).…”
Section: Discussionsupporting
confidence: 92%
“…Pengumpulan data dalam seluruh studi menggunakan kuesioner dan ada 1 studi yang diikuti dengan wawancara. Sebanyak 3 studi berasal dari Pakistan (15)(16)(17), 2 studi dari Brazil (9,18), 2 studi dari Arab (19,20), serta masing-masing 1 studi berasal dari Taiwan (21), Kenya(1), India (22), Israel (13), Italia (23), dan Vietnam (24). Populasi studi terdiri dari mahasiswa kedokteran gigi, dokter gigi, dan perawat gigi.…”
Section: Metodeunclassified
“…Tenaga kesehatan yang lebih tua mengalami kecemasan yang lebih besar terhadap keselamatan diri sendiri, keluarga, dan pasien tetapi tetap mempertahankan kewajiban profesional kerja. Selain itu, peningkatan stres berkaitan dengan kurangnya jumlah APD(17).…”
unclassified
“…Poor PPE use practices in dental institutions were also reported by studies in many other countries. A survey conducted in Pakistan showed that only 50% of dentists have compliance with PPE wear ( 18 ). An Indian study revealed a dearth of understanding on the proper use of PPE in dental treatment ( 19 ).…”
Section: Introductionmentioning
confidence: 99%